Kombinasi Metode Multi-Attribute Utility Theory dan Pivot Pairwise Relative Criteria Importance Assessment Dalam Penentuan Lulusan Terbaik - Ainaya Qintan Maharani; Temi Ardiansah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The determination of the best graduates at SMK YPT Pringsewu is determined based on the average score, achievement, and report card score. By using this assessment, the school takes a long time with a large number of prospective graduates to complete and select all prospective graduates and determine the best graduates. So it requires a recommendation system in determining the best graduates, one of the recommendation systems for determining the best graduates is a decision support system. With the decision support system for determining the best graduates, it will speed up the process of determining the best graduates because it uses a computerized system. This study aims to develop a decision support system that applies the MAUT method and the PIPRECIA method in determining the best graduation in school and develop an objective system or approach to assess and rank the best graduates based on relevant criteria and preferences set by researchers or related parties. PIPRECIA and MAUT methods are used to overcome complexities in multi-criteria decision making and help select the best graduates effectively. The results of determining the best graduate students using the MAUT method and PIPRECIA recommended Mareta Amelia as the best graduate student in school because the final ranking results got Rank 1 with a total score of 0.642. The overall results for testing using the blackbox testing model with results are 100% in accordance with the functionality of the system for the determination of the best graduates.